2007
DOI: 10.1007/s10826-007-9170-1
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory Factor Analysis of Arnold et al.’s Parenting Scale Across Race, Age, and Sex

Abstract: We used confirmatory factor analysis (CFA) to investigate the factor structure of several models of Arnold et al. 's Parenting Scale [Arnold et al. (1993). Psychological Assessment, 5, 137-144] across children from various age groups and races. Participants were parents of children (ages 2-16 years) presenting to four community-based pediatric practices for routine care. Parents completed questionnaires pertaining to various aspects of parenting and child behavior problems. Results indicated that a two-factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 30 publications
(88 reference statements)
5
24
1
Order By: Relevance
“…When Overreactivity and Laxness were controlled, Verbosity did emerge as a statistically significant, but very weak and probably clinically irrelevant, predictor of child problem behavior in the sample of mothers. This is not the first study, which fails to support the Verbosity factor (Collett, et al 2001;Irvine, et al 1999;Karazsia, et al 2008;Prinzie, et al 2007;Steele, et al 2005). It was suggested that verbosity might only be a relevant factor for parents with very young children who have not yet developed the necessary language skills to understand verbal reasoning (Rhoades and O'Leary 2007).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…When Overreactivity and Laxness were controlled, Verbosity did emerge as a statistically significant, but very weak and probably clinically irrelevant, predictor of child problem behavior in the sample of mothers. This is not the first study, which fails to support the Verbosity factor (Collett, et al 2001;Irvine, et al 1999;Karazsia, et al 2008;Prinzie, et al 2007;Steele, et al 2005). It was suggested that verbosity might only be a relevant factor for parents with very young children who have not yet developed the necessary language skills to understand verbal reasoning (Rhoades and O'Leary 2007).…”
Section: Discussionmentioning
confidence: 84%
“…The third set of studies (Karazsia, et al 2008;Rhoades and O'Leary 2007;Steele, et al 2005) utilized confirmatory factor analyses only. They tested the fit indices for the models identified in earlier studies.…”
Section: Later Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Items are scored on a 7-point Likert scale, with higher scores indicating less effective parenting styles. The present study focused on laxness and over-reactivity: the stability and good psychometric properties of these two factors have been demonstrated across a broad age range of children (Karazsia et al, 2008). These scales had satisfactory internal consistency: alphas for the Phase 1 and Phase 2 SEN groups were 0.71 and 0.79 for laxness and 0.70 and 0.78 for over-reactivity, respectively.…”
Section: Parenting Stylementioning
confidence: 78%
“…Parents self-report, on a scale of 1-7, the intensity with which they participate in particular behaviors when disciplining their children. Recent factor analyses support two scales: Laxness and Overreactivity (Karaszia, van Dulmen, & Wildman, 2008;Reitman et al, 2001). Both scales contain five items and range from 5 to 35.…”
Section: Demographic Questionnairementioning
confidence: 99%